Σύστημα εντοπισμού υποβρυχίου ρομποτικού οχήματος - Αλ Ναγκάρ, Φάτμα (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
The main objective of this project is to develop a localization system for an underwater robot (ROV), the VideoRay Pro-4 in a tank which is situated in the building of Sikopetritis CYPRUS UNIVERSITY OF TECHNOLOGY (CUT). The main objective of this work is the positioning of the underwater robot through visual indicators placed at a priori known positions in the tank and using the robot’s camera, utilizing the indicator’s images on the Charge Coupled Device (CCD). Also in this project we develop the methodology for finding unknown vision system parameters in order to calibrate the vision system for the localization task. First we perform mathematical analysis of the problem and modelling of the physical phenomena that take place and then developing the solution methodology. The developed methodology is coded in the Octave programming language and then wrapped in the programming language C/C++. The developed methodology is implemented the in the Robotic Operation System (ROS) to carry out the experiment. Finally, creating indicators, patterns and a calibration base where the robot will be placed in the tank for calibration and vision system parameter identification experiments. The importance of this research is that the system developed can be utilized in the underwater positioning of the ROV, which is an important aspect of carrying out underwater operations.
Keywords: Underwater Robot; Visual Indicators; Charge Coupled Device; Octave Programming Language; Υποβρύχιο Ρομπότ; Οπτικοί Δείκτες; Συσκευή Συζευγμένου Φορτίου; Γλώσσα Προγραμματισμού Octave